2014
DOI: 10.3184/175815514x14162394225987
|View full text |Cite
|
Sign up to set email alerts
|

Great Tits Build Shallower Nests than Blue Tits

Abstract: Comparative studies predicted or reported weaker or stronger positive relationships between nest size and body size both within and across avian species. Here we show that in relatively small nest-chambers, larger Great Tits (Parus major) build shallower nests than smaller Blue Tits (Cyanistes caeruleus). Our results from the Mediterranean region support findings from published studies that were conducted at more northerly latitudes (UK and Poland). Potential impacts of the local climate and predation risks on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…This concurs with a number of previous nest box studies, though not all (Lambrechts et al 2016b), and may be linked to adult quality (Alvarez et al 2013;Gladalski et al 2016;Lambrechts et al 2016a). Such differences in turn may be linked to differences in nesting behaviour and reproductive output between these species, as Blue Tits typically build proportionally heavier nests and have a higher average reproductive output per breeding attempt than the larger Great Tit (Lambrechts et al 2014(Lambrechts et al , 2015Gladalski et al 2016).…”
Section: Discussionsupporting
confidence: 76%
“…This concurs with a number of previous nest box studies, though not all (Lambrechts et al 2016b), and may be linked to adult quality (Alvarez et al 2013;Gladalski et al 2016;Lambrechts et al 2016a). Such differences in turn may be linked to differences in nesting behaviour and reproductive output between these species, as Blue Tits typically build proportionally heavier nests and have a higher average reproductive output per breeding attempt than the larger Great Tit (Lambrechts et al 2014(Lambrechts et al , 2015Gladalski et al 2016).…”
Section: Discussionsupporting
confidence: 76%
“…If the larger Great Tits would require a longer safety distance than the smaller Blue Tits (C. c. ogliastrae) (cf. Lambrechts et al, 2014), we expected thinner nests in Great Tits than in Blue Tits. If the individuals with the earlier and larger clutches would require, or be able to produce, thicker nests (cf.…”
Section: Introductionmentioning
confidence: 86%
“…By contrast, three published field investigations from distinct climate regions show shallower, and smaller, nests in the larger Great Tits than in the smaller Blue Tits (Smith et al, 2013;Kaliński et al, 2014;. Lambrechts et al (2014) suggested that the two species might perceive and experience external abiotic or biotic factors differently, which is subsequently reflected in how the nest is built. The height (or depth) and size of fresh nests is also adjusted to the depth of the chamber (Mazgajski and Rykowska, 2008;Smith et al, 2013;Kaliński et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations